Margaret Shaida: The Legendary Cuisine of Persia - Saberi, Helen J (Petits Propos Culinaires, 1993)
Margaret Shaida: The Legendary Cuisine of Persia: Lieuse Publications (Della Ra, Harpsden Way, Henley-upon-Thames, Oxfordshire RG9 lNL), 1992: 325 pp, 6 colour photos, b/w illustrations by Melanie Kaveh, glossary and index, foreword by Alan Davidson, introduction by Gregory Lima, £19.00.